Geotechnical Properties of Uncompacted DNA-1A Lunar Simulant - Marzulli, Valentina; Cafaro, Francesco (Journal of Aerospace Engineering, 2019)
Understanding the mechanical behavior of lunar regolith is of great importance to address the building of structures on the Moon, as well as for predicting the response of some equipment or facilities interacting with the lunar soil (i.e., rovers). Because the number of lunar regolith samples on Earth is quite low due to the difficulties of bringing it back during space missions, in the last decades, researchers started to develop similar materials, usually named lunar regolith simulants. This paper reports the geotechnical characterization of the De NoArtri (DNA) lunar simulant carried out in the laboratory. Compositional analyses and mechanical tests have been carried out to characterize this simulant; particle-size distribution analysis, chemical analysis, and scanning electron microscope (SEM) analysis have been performed to identify the DNA-1A from a compositional point of view, as well as triaxial compression, direct shear, and oedometer tests for depicting its mechanical behavior, with some comparison with original lunar soil and other simulants.
CRIS-Team Scopus Importer:2019-12-03
Keywords: DNA simulant; Loose behavior; Lunar simulant; Lunar soil; Lunar structures; Moon